Characteristics and Profiles of Moped Crashes in Urban Areas: An In-Depth Study. Issue 34 (December 2018) - Ceunynck, Tim De; Slootmans, Freya; Daniels, Stijn
In this in-depth study, 167 severe injury crashes involving a moped in urban areas in Belgium in 2013 are analyzed. The study provides an overview of the general crash characteristics of and contributing factors to these moped crashes, and identifies typical crash profiles and their characteristics. The representation of class A mopeds (maximum speed 25 km/h [16 mph]; no driving license needed) and class B mopeds (maximum speed 45 km/h [28 mph]; driving license required) in these crashes is approximately fifty-fifty, which seems to imply an over-representation of mopeds class A. The involved moped riders have an average age of 33 and three-quarters are men. Human factors are by far the largest category of contributing factors in moped crashes, factors related to infrastructure and environment play a moderate role, and vehicle-related factors play only a minor role. The most important human factors are psychological factors and risk assessment errors, the main non-human contributing factors are sight obstructions owing to infrastructure or other vehicles. The following crash profiles, grouping similar types of crashes, were identified: crashes between a vehicle turning off and a moped going straight through (18%); crashes caused by the moped rider's risky behavior (17%); crashes between a moped and another vulnerable road user (13%); crashes resulting from entering or exiting destinations alongside the road (12%); crashes at intersections (other than vehicles turning off) (11%); single-vehicle crashes with loss of control (9%); crashes caused by an error during overtaking (8%); rear-end crashes (3%); and other (9%).